Network Pharmacology, Molecular Docking Analysis and Molecular Dynamics Simulation of Scutellaria baicalensis in the Treatment of Liver Fibrosis - Wang, Junrui; Wu, Zhuoqing; Chen, Xiaolei; Sun, Ying; Ma, Shuyao; Weng, Jingdan; Zhang, Yuxin; Dong, Keke; Shao, Jiangjuan; Zheng, Shizhong (Current pharmaceutical design, 2024)
Traditional Chinese medicine (SB), one of the clinical firstline heat-clearing drugs, has obvious symptomatic advantages for hepatic fibrosis with dampness-heat stasis as its syndrome. We aim to predict and validate the potential mechanism of active ingredients against liver fibrosis more scientifically and effectively. The underlying mechanism of in inhibiting hepatic fibrosis was studied by applying network pharmacology, molecular docking and molecular dynamics simulation. Expression levels of markers in activated Hepatic Stellate Cells (HSC) after administration of three extracts were determined by Western blot and Real-time PCR, respectively, in order to verify the anti-fibrosis effect of the active ingredients Results: There are 164 common targets of drugs and diseases screened and 115 signaling pathways obtained, which were mainly associated with protein phosphorylation, senescence and negative regulation of the apoptotic process. Western blot and Real-time PCR showed that extracts could reduce the expression of HSC activation markers, and Oroxylin A had the strongest inhibitory effect on it. Molecular docking results showed that Oroxylin A had high binding activity to target proteins. Molecular dynamics simulation demonstrates promising stability of the Oroxylin A-AKT1 complex over the simulated MD time of 200 ns. active ingredients may inhibit HSC proliferation, reduce the generation of pro-inflammatory factors and block the anti-inflammatory effect of inflammatory signal transduction by inducing HSC apoptosis and senescence, thus achieving the effect of anti-fibrosis.